Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations IN SEASON — ALWAYS. For the Home. For the Sickroom. For the Bath. USE LYSOL (GADD). Also for SURGICAL and NURSING PURPOSES, DENTAL USE and to DISINFECT LINEN and CLOTHING and as a GENERAL DISINFECTANT Ask Your Chemist for "Caerwisc" Brand. Eau de Cologne Refreshing, Cooling, Delightful. A high-class Eau-de-Cologne of pleasing fragrance EVERY SICK ROOM SHOULD BE SPRAYED WITH CAERWISC COLOGNE Should any difficulty arise in obtaining the above lines write direct to the SOLE MANUFACTURERS SAMPLES FREE to the MEDICAL PROFESSION. Evans, Gadd & Co., Ltd., BRISTOL and EXETER. [Picture] E. T. CURTIS & SON, College Avenue, Magdalen Road, EXETER BUILDERS, CONTRACTORS, UNDERTAKERS, HEATING, LIGHTING & DOMESTIC ENGINEERS. DECORATORS, &c. Estimates Free. Work executed by an efficient staff of skilled workmen. SEND US YOUR ENQUIRIES. Private Address : LESADOR, DENMARK ROAD, EXETER. Phone 3186. 68 292/841.51/2/2